The Homiletical Plot : The Sermon as Narrative Art Form - Lowry, Eugene L. (Louisville, Ky. : Westminster John Knox Press, 2001)
"Now in a reissue with a new foreword by Fred B. Craddock and an afterword by the author, Eugene L. Lowry, The Homiletical Plot, Expanded Edition follows in the same solid tradition of its predecessor. Upon its release, The Homiletical Plot quickly became a pivotal work on the art of preaching. Instead of comments on a biblical passage, Lowry suggested that the sermon follow a narrative form that moves from beginning to end, as with the plot of a story. This expanded edition continues to be an excellent teaching resource and learning tool for all preachers from introductory students to seasoned clergy."--Jacket.
The sermon as narrative. The image of the sermon ; Getting started ; Plot forms -- The stages of the homiletical plot. Upsetting the equilibrium ; Analyzing the discrepancy ; Disclosing the clue to resolution ; Experiencing the gospel ; Anticipating the consequences -- Other considerations. Variations ; Preparation ; Biblical narrative preaching.
Revised edition of: The homiletical plot. Atlanta : John Knox Press, c1980.
Includes bibliographical references (pages 135-138).
Keywords: Preaching - Homiletics; Storytelling - Narrative Art Form -- Religious aspects -- Christianity